A episteme moderna, o emergir e a crise da Psicologia científica - Macedo, Jhonatan Dhimmy Fraga (2021)
This work aims to investigate how the modern epistemological framework contributes to the emergence of Scientific Psychology. Specifically, it will inquire about the kantian philosophical revolution and the hegelian historical and dialectical theoretical proposals, and describe how these two biases impact, in general, the XIX’s century episteme, which enables the emergence of Psychology as a science. In the first chapter it will be presented the process of how the change in the conception of knowledge in the Modern age contributed to a new conception of subjectivity. In the second chapter it will be exposed the logic-formal kantian bias and its implications to the consolidation of classical science and how this opens the doors to the emergence of a Scientific Psychology at the XIX century. It will be argued that the kantian bia conditions general contemporary thinking, and Psychology specifically, and that it’s an important paradigm which grounds later epistemologies, specially in Psychology. In the last chapter it will be presented the onto-logic bias, developed by Hegel, and its implications to Psychology. Going from Hegel’s criticism on Modern thought, and Kant specifically, will be proposed that Humanities, and most specifically Psychology, show worry as men’s being, and not only it’s way of being or way of knowing - as the kantian influenced Psychology did.